Late‐onset extensive haematoma mimicking cellulitis. Issue 1 (31st October 2018) - Baek, Yoo S.; Song, Jin Y.; Jeong, Kyung M.; Jeon, Jiehyun
Abstract : Cellulitis is a microbial infection of the deep dermis and the subcutaneous tissue. Several non‐infectious disorders, such as contact dermatitis, insect bites, stasis dermatitis, and lipodermatosclerosis, masquerade as infectious cellulitis. There are no specific criteria for the diagnosis of cellulitis; thus, it is challenging to correctly diagnose true cellulitis. For previously assumed cellulitis cases that were refractory to conventional antimicrobial treatment, thoroughly investigating the circumstances of symptom initiation, recording the medical history, and performing an attentive physical examination of the patient is critical for distinguishing true cellulitis from conditions that mimic cellulitis. The inquiry should be personalised according to the patient's age and the prescribed medication. Furthermore, imaging studies, including ultrasonography and magnetic resonance imaging, should be considered on certain occasions to non‐invasively aid the differential diagnosis.